2020
DOI: 10.1002/pol.20190205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polymer and ion concentration on mechanical and drug release behavior of gellan hydrogels using factorial design

Abstract: Developing optimized hydrogel products requires an in-depth understanding of the mechanisms that drive hydrogel tunability. Here, we performed a full 4 × 4 factorial design study investigating the impact of gellan, a naturally derived polysaccharide (1%, 2%, 3%, or 4% w/v) and CaCl 2 concentration (1, 3, 7, or 10 mM) on the viscoelastic, swelling, and drug release behavior of gellan hydrogels containing a model drug, vancomycin. These concentrations were chosen to specifically provide insight into gellan hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
4
5
0
Order By: Relevance
“…Thus, Cur_11% had the highest values of Young’s modulus (0.296 ± 0.036 MPa) and tensile strength (0.051 ± 0.008 MPa), which indicates its higher stability compared to the other tested biomaterials. This observation is in accordance with results presented by other researchers, as the hardness and stiffness of the biomaterials increased with greater concentration of polymer in the sample [ 69 , 70 ].…”
Section: Resultssupporting
confidence: 93%
“…Thus, Cur_11% had the highest values of Young’s modulus (0.296 ± 0.036 MPa) and tensile strength (0.051 ± 0.008 MPa), which indicates its higher stability compared to the other tested biomaterials. This observation is in accordance with results presented by other researchers, as the hardness and stiffness of the biomaterials increased with greater concentration of polymer in the sample [ 69 , 70 ].…”
Section: Resultssupporting
confidence: 93%
“…It is evident from the results that as the concentration of polymer in formulation increases a large hydrogel network was observed. The possible reason was that the large network diffuses more drugs from the hydrogel network and improves drug release [ 27 ]. Same results have been seen by Dong et al, worked who created dual cross-linked hydrogel in which polymer concentration increased drug release [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…A similar mechanism was previously described for gellan-based hydrogels, whose crosslinking is similarly mediated by the interaction with Ca 2+ ions. [73] The ability of bioinks to tolerate the extrusion process, and their ability to retain the predetermined geometry for the duration of the designed experimental activities, have to be considered as primary requisites. The bioinks presented in this study were shown to fulfill these requirements.…”
Section: Discussionmentioning
confidence: 99%